Assessing the topical application efficiency of two biological agents in managing chemotherapy-induced oral mucositis in children: A randomized clinical trial - Muaaz Alkhouli; Mohannad Laflouf; John C. Comisi (Elsevier, 2021)
Background: oral mucositis is one of the most annoying complications of chemotherapy. This randomized clinical trial aimed to assess the efficiency of Aloe Vera and Olive Oil in managing chemotherapy-induced oral mucositis. Methods: 36 children between 6 and 9 years and suffering from grade 3 or 4 oral mucositis, according to the World Health Organization (W.H.O.) scale, were enrolled in this clinical trial. Participants were separated into three groups to treat their mucositis using Aloe Vera, Olive Oil, or sodium bicarbonate. Nurses administrated the agents four times daily with sponge sticks. Two blinded investigators examined the oral mucosa after ten days. Results: Both Aloe Vera and Olive Oil significant differences in the management of chemotherapy-induced oral mucositis compared to sodium bicarbonate treatments. Conclusions: Olive Oil is effective in managing CIOM.